Simulation of Magnetotargeting of Medicines Based on the Calculation of Permeability of Human Tissues by the Electromagnetic Field - A. V. Churakov; P. V. Kamlach; A. I. Ongarbayeva (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2023)
Analysis of studies in the field of targeted delivery of drugs, genes and stem cells showed a low level of accuracy of both applied and practical research in this area. Sufficiently encouraging results were obtained with extracorporeal electromagnetic action on a pharmacological complex with a ferromagnetic nanoparticle. With this approach, it is rather difficult to implement the algorithm for introducing the drug into the topographic region (target organ), since in practice, approaches to the clinical application of drug transport technology, taking into account the physicochemical properties of human body tissues, have not been studied in detail. The available models represent various physical and mathematical approaches that do not take into account the bioelectrical and electrostatic properties of the tissues of the organisms of experimental animals and humans. The creation of algorithms and software simulation of this technology will allow calculating variable frequency variables for magnetotargeting in a human digital phantom, which will reduce time spent at the stage of pilot and clinical trials and in the future will form the applied part of the innovative technology. The article presents the methodology and results of multiphysics and mathematical modeling in the Sim4Life for Science, V7.0 package on the example of calculating the control parameters of the electromagnetic field of the region in the area of normal administration of drugs – the vessels of the forearm.